4m-5=2m-23

Simple and best practice solution for 4m-5=2m-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m-5=2m-23 equation:


Simplifying
4m + -5 = 2m + -23

Reorder the terms:
-5 + 4m = 2m + -23

Reorder the terms:
-5 + 4m = -23 + 2m

Solving
-5 + 4m = -23 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
-5 + 4m + -2m = -23 + 2m + -2m

Combine like terms: 4m + -2m = 2m
-5 + 2m = -23 + 2m + -2m

Combine like terms: 2m + -2m = 0
-5 + 2m = -23 + 0
-5 + 2m = -23

Add '5' to each side of the equation.
-5 + 5 + 2m = -23 + 5

Combine like terms: -5 + 5 = 0
0 + 2m = -23 + 5
2m = -23 + 5

Combine like terms: -23 + 5 = -18
2m = -18

Divide each side by '2'.
m = -9

Simplifying
m = -9

See similar equations:

| -9-(p/4)=5 | | 4x^2-12=4x^2-12 | | 6x+19x+-4=5(5x+4) | | [x-3]=4x-7 | | -1=y-8 | | 5(-Y+(-2))+3Y=-11 | | 8.7+n=10.4 | | -11a=-29 | | 42s+11-3=49 | | 7/9x-3=18 | | n+84=-100 | | 5(p+3)+9=3(p-2)+b | | -6a-2-5a=-31 | | 10z^2-37z-36=0 | | y=14/lnx | | (4x-.1)(4x+.1)= | | x+6x=24.5 | | 3y^2-3x=0 | | -14+x=-25 | | (x-(5/7))/x=1/7 | | 9t-3t=n | | 1/4c=20 | | 2/(3(x-8))=18 | | h=gv | | 100-2(x+3)=-20+x | | ln(x+5)=8 | | 2x(90)= | | 2v=15v-117 | | 3x+10=8x-5 | | 7z+8=3z+8 | | 8x-x=49 | | (3n-64)1/2=(n/3)1/2 |

Equations solver categories